Penerapan Analisis Biplot pada Pemetaan 35 Kabupaten/Kota di Provinsi Jawa Tengah Berdasarkan Karakteristik Ekonomi dan Kependudukan - Danang Kuswardono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze and map 35 districts/cities in Central Java Province based on economic and population characteristics using the biplot analysis approach. The economic and population characteristics used are population density (X1), Human Development Index (X2), Gross Regional Domestic Product (X3) growth rate, poverty rate (X4), and open unemployment rate (X5). The data used in this study are economic and population data from each district/city obtained from BPS RI (Statistics Indonesia). The biplot analysis method is used to extract patterns and relationships between economic and population variables and visualize the relative positions of each district/city in the figure. The mapping generated by the biplot analysis can provide insights for policymakers in the planning and development of regions in Central Java. Based on the biplot analysis, it was found that Klaten, Sukoharjo, Kudus, Tegal, the city of Magelang, the city of Surakarta, the city of Salatiga, the city of Semarang, the city of Pekalongan, and the city of Tegal have similarities in characteristics of high population density. The cities of Surakarta, Magelang, Semarang, Pekalongan, Salatiga, Tegal, Sukoharjo, Klaten, Karanganyar, and Kudus are similar because of their relatively higher Human Development Index values compared to other areas. Districts/cities that are similar due to their high Gross Regional Domestic Product (GRDP) growth rates are Boyolali, the city of Surakarta, Karanganyar, and Klaten. Meanwhile, Sragen, Demak, Purworejo, Magelang, Grobogan, Purbalingga, Kebumen, Banjarnegara, Wonosobo, Kendal, and Brebes have similarities in terms of higher poverty levels. Meanwhile, based on the characteristics of the open unemployment rate, there are Tegal regency, Cilacap regency, and Kendal city.